An Exploration of Volition: Caregiver Perceptions of Persons with Dementia - Christine Raber, PhD, OTR/L; Mikel Stone, MOT, OTR/L (Scholarworks @ WMU, 2015)
The purpose of this study was to understand what formal caregivers know about the volition of older adults with moderate dementia. A qualitative approach was used at one assisted living facility. Semi-structured interviews were conducted with formal caregivers to gain their perceptions of residents' volition or motivation for occupation. Volition of resident participants was assessed using the Volitional Questionnaire (VQ). Caregiver interviews and resident VQ's were analyzed using van Manen's phenomenological approach to examine their congruence with regard to the volitional abilities of residents. Thematic analysis yielded two broad themes: (a) Caregivers possess varying layers of insight regarding the volitional abilities of the older adults with dementia, and (b) caregivers develop a script regarding the volitional abilities of the older adults with dementia. Caregivers possess knowledge about volitional abilities of older adults with dementia. Further research is needed to understand how these perceptions affect their care-giving behaviors.